Prevention of ulcerative colitis by Huangqin decoction: reducing the intestinal epithelial cell apoptosis rate through the IFN-γ/JAK/ETS signalling pathway - Xiaowei Mo; Kairui Tang; Lijing Deng; Xingyi Zhou; Xiaojuan Li; Yupei Zhang; Jing Wang (Taylor & Francis Group, 2022)
Context Ulcerative colitis (UC) is a chronic idiopathic inflammatory bowel disease that is closely related to inflammation and apoptosis. The traditional Chinese medicine compound preparation Huangqin decoction (HQD) has been widely used in the clinical treatment of UC, but the specific mechanism of its function is still inconclusive.Objective To explore the pathogenesis of UC based on the IFN-γ/JAK/ETS signalling pathway, and to clarify the biological mechanism of HQD.Materials and methods Forty 8-week-old male C57BL/6 mice were randomly divided into four groups: normal control, model, model + salazosulfapyridine group (500 mg/kg, p.o., pd) and model + HQD (9.1 g/kg, p.o., pd). Using Dextran sulphate sodium (DSS) salt (2.5%, p.o.)+high-fat diet + hot and humid environment to build a mouse model of UC. One month later, the changes of colon morphology, serum inflammatory factors, intestinal epithelial cell apoptosis and IFN-γ/JAK/ETS signalling pathway related protein changes in mice were observed.Results Compared with the model group, HQD significantly reduced the pathological score of the model mice's colon (2.60 ± 0.25 vs. 4.80 ± 0.37), and reduced the serum IFN-γ (200.30 ± 8.45 vs. 413.80 ± 6.97) and other inflammatory factors, and reduced intestinal epithelial cell apoptosis (24.85 ± 4.87 vs. 214.90 ± 39.21). In terms of mechanism, HQD down-regulated IFN-γ/JAK/ETS signalling pathway related proteins in colon tissue of UC model mice.Conclusions These data indicate that HQD can improve UC by reducing intestinal inflammation and apoptosis, providing experimental evidence for the wide application of HQD in clinical practice of UC.